2019
DOI: 10.5664/jcsm.8086
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Presentation of REM Sleep Behavior Disorder: The Relative Importance of Sex, Associated Neurological Disorder, and Context of Referral to Polysomnography

Abstract: Study Objectives: To identify the interrelation and relative influence of sex, associated neurological disorder, and polysomnography (PSG) context on the manifestations of rapid eye movement (REM) sleep behavior disorder (RBD). Methods: Fifty-seven patients with RBD were assessed with video PSG regarding sleep structure, muscular activity, and motor events (ME) during REM sleep. Patients were categorized according to sex, associated neurological disorder (clinically isolated RBD [iRBD] versus RBD associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
10
2
Order By: Relevance
“…37 If the motor activity during REM sleep is more vigorous in men, 38,39 then it is possible that RBD may be noticed earlier in men. The underlying pathophysiology for such a difference is not understood, but increased REM sleep-phasic muscle activity in men, [40][41][42] and sex differences in the types of motor movements 40 may be contributing factors. Although RBD is a strong predictor of probable DLB, 17,18,36 it is possible that a more subtle expression of RBD, perhaps more common in women, may be under-reported or unrecognized without routine polysomnography.…”
Section: Discussionmentioning
confidence: 99%
“…37 If the motor activity during REM sleep is more vigorous in men, 38,39 then it is possible that RBD may be noticed earlier in men. The underlying pathophysiology for such a difference is not understood, but increased REM sleep-phasic muscle activity in men, [40][41][42] and sex differences in the types of motor movements 40 may be contributing factors. Although RBD is a strong predictor of probable DLB, 17,18,36 it is possible that a more subtle expression of RBD, perhaps more common in women, may be under-reported or unrecognized without routine polysomnography.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a polysomnographic study investigating motor features of sleep behaviours reported that men have higher EMG phasic activity, more myoclonic movements, and more movements involving the trunk, whereas segmental movements were more frequent in women (Bugalho & Salavisa, 2019). Another polysomnographic study investigating RWA in both legs and arms, reported a higher RWA index in the legs in men compared with women, and a higher RWA index in the arms in women.…”
Section: Sex Issues Inrbdmentioning
confidence: 70%
“…Bugalho and Salavisa reported the influence of referral reason for RBD diagnosis on the global severity of motor events during REM sleep. 26 Patients who were directly referred because of RBD symptoms showed a higher severity of motor events during REM sleep than did those with RBD who were referred after screening procedure or during clinical follow-up for other disorders. In most of our patients, RBD symptoms were identified after screening procedures for the differential diagnosis of DLB in memory clinics.…”
Section: Importance Of Proactive and Comprehensive Sleep History Evaluationmentioning
confidence: 89%
“…The authors emphasised the potential selection bias in different clinical settings. Bugalho and Salavisa reported the influence of referral reason for RBD diagnosis on the global severity of motor events during REM sleep 26 . Patients who were directly referred because of RBD symptoms showed a higher severity of motor events during REM sleep than did those with RBD who were referred after screening procedure or during clinical follow‐up for other disorders.…”
Section: Discussionmentioning
confidence: 99%